European Paediatric Surgeons' Association Survey on the Adherence to EAU/ESPU Guidelines in the Management of Undescended Testes - Aubert, Ophelia; Zaidan, Hind; Garnier, Hanna; Saxena, Amulya K.; Cascio, Salvatore (European Journal of Pediatric Surgery, 2023)
Introduction The aim of this study was to assess the adherence to the European Association of Urology (EAU)/European Society for Pediatric Urology (ESPU) 2016 guidelines in the management of undescended testes (UDT).Materials and Methods An online questionnaire was sent in 2023 to members of the European Paediatric Surgeons' Association (EUPSA).Results Among 157 members, 46 and 44% perform orchidopexy before 12 and 18 months, respectively. In total, 92% recommend conservative management of retractile testes and 58% offer close follow-up. In case of nonpalpable testes, 78% favor laparoscopy and 18% ultrasonography. If a peeping testicle is identified at laparoscopy, 76% perform a single-stage orchidopexy. In case of a high testicle, a staged procedure is preferred (84%). Management of blind-ending spermatic vessel is heterogenous with a majority ending the operation, followed by exploration of the inguinal canal and removal of the testicular nubbin with optional fixation of the contralateral testis. Only a minority recommends hormonal therapy to improve fertility potential in bilateral UDT. A majority (59%) discuss testis removal in UDT in postpubertal boys. In addition, 77% declare following the EAU/ESPU guidelines. Unawareness of guidelines was the most common reason cited for nonadherence. International guidelines were found to have the greatest influence on clinical practice; however, personal experience and institutional practice seem to play an important role.Conclusion Most recommendations of the EAU/ESPU guidelines are being followed by EUPSA members; however, personal and institutional practice impact decision making. Hormonal therapy in bilateral UDT, management of vanishing testes, and UDT in postpubertal boys could be improved.
Keywords: undescended testis; cryptorchidism; pediatric surgery; practice patterns; guidelines